Enhancing Indonesian EFL Learners' Vocabulary Mastery Through Realia at MA Al-Khoirot - Rohma, Roudhotur; Mulis, Mulis (Journal of English Language and Education, 2026)
This study aims to investigate the effectiveness of using regalia in improving tenth-grade students’ vocabulary mastery in an Indonesian EFL madrasah context and to explore students’ responses to this approach. Vocabulary mastery is essential for EFL proficiency, yet Indonesian madrasah students frequently face challenges due to reliance on rote memorization and textbook-centered instruction, resulting in limited retention and low motivation. While multisensory techniques such as realia have demonstrated success with younger learners, their implementation at the senior high school level has been limited. This classroom action research was conducted over two cycles with 29 female tenth-grade students at MA Al-Khoirot Malang. Data was gathered through tests, observations, field notes, worksheets, and interviews. Findings revealed significant improvement: mean scores increased from 49.0 (with 0% meeting the minimum criterion of ≥75) to 72.8 by Cycle 2, when nearly 80% of students achieved the criterion. Students showed active engagement, spontaneous use of new vocabulary, and high enthusiasm, attributing their positive responses to realia’s tactile, relevant, and collaborative features. The study concludes that realia is a practical, low-cost, and highly effective tool for enhancing vocabulary mastery in Indonesian EFL madrasah settings.